Diffraction enhanced kinetic depth X-ray imaging - Dicken, Anthony (Department of Engineering and Applied Science, 2013)
An increasing number of fields would benefit from a single analytical probe that can characterise bulk objects that vary in morphology and/or material composition. These fields include security screening, medicine and material science. In this study the X-ray region is shown to be an effective probe for the characterisation of materials. The most prominent analytical techniques that utilise X-radiation are reviewed. The study then focuses on methods of amalgamating the three dimensional power of kinetic depth X-ray (KDFX) imaging with the materials discrimination of angular dispersive X-ray diffraction (ADXRD), thus providing KDEX with a much needed material specific counterpart. A knowledge of the sample position is essential for the correct interpretation of diffraction signatures. Two different sensor geometries (i.e. circumferential and linear) that are able to collect end interpret multiple unknown material diffraction patterns and attribute them to their respective loci within an inspection volume are investigated. The circumferential and linear detector geometries are hypothesised, simulated and then tested in an experimental setting with the later demonstrating a greater ability at discerning between mixed diffraction patterns produced by differing materials. Factors known to confound the linear diffraction method such as sample thickness and radiation energy have been explored and quantified with a possible means of mitigation being identified (i.e. via increasing the sample to detector distance). A series of diffraction patterns (following the linear diffraction appoach) were obtained from a single phantom object that was simultaneously interrogated via KDEX imaging. Areas containing diffraction signatures matched from a threat library have been highlighted in the KDEX imagery via colour encoding and match index is inferred by intensity. This union is the first example of its kind and is called diffraction enhanced KDEX imagery. Finally an additional source of information obtained from object disparity is explored as an alternative means of calculating sample loci. This offers a greater level of integration between these two complimentary techniques as object disparity could be used to reinforce the results produced by the linear diffraction geometry.
Keywords: X-ray imaging; X-ray diffraction; Materials; Physics